1989
DOI: 10.1007/bf01014732
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition stimulants of an Aristolochiaceae-feeding swallowtail butterfly,Atrophaneura alcinous

Abstract: Oviposition stimulants of an Aristolochiaceae-feeding swallowtail butterfly,Atrophaneura alcinous, were isolated from the leaves ofAristolochla debilis and characterized as a mixture of aristolochic acids and sequoyitol. An artificial blend of these components applied to filter paper induced a significant oviposition response by the female butterflies, identical to that elicited by intact leaves of theAristolochia host plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 15 publications
2
67
0
Order By: Relevance
“…[18][19][20] Likewise, larvae of an Aristolochiaceae-feeding swallowtail, A. alcinous, were found to be stimulated by the hostspecific secondary metabolites 17 together with unknown cofactors. 14,21) These facts suggested a congruent sensory mechanism between the tarsal chemoreceptors of adults and the gustatory chemoreceptors of larvae towards hostspecific plant allelochemicals. However, the nature of such chemosensory processes at both larval and adult stages is not well understood.…”
Section: Larval Phagostimulants Of Swallowtail Butterfliesmentioning
confidence: 90%
See 2 more Smart Citations
“…[18][19][20] Likewise, larvae of an Aristolochiaceae-feeding swallowtail, A. alcinous, were found to be stimulated by the hostspecific secondary metabolites 17 together with unknown cofactors. 14,21) These facts suggested a congruent sensory mechanism between the tarsal chemoreceptors of adults and the gustatory chemoreceptors of larvae towards hostspecific plant allelochemicals. However, the nature of such chemosensory processes at both larval and adult stages is not well understood.…”
Section: Larval Phagostimulants Of Swallowtail Butterfliesmentioning
confidence: 90%
“…2) The oviposition stimulants of another Apiaceae-feeder, P. polyxenes, were identified as a blend of a malonylated flavone glycoside (14), tyramine (15), and chlorogenic acid (16). 10,11) The synergistic effects of combinations of flavonoids, hydroxycinnamates, and phenethylamine derivatives appeared to be a common feature of oviposition stimulant system among these two closely related butterfly species, even though the host-plant taxa (Apiaceae and Rutaceae) are remote to each other.…”
Section: Plant Metabolites As Host-finding Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Distilled water was sprayed onto the plant model to help the female detect the leaf extract (Honda, 1986;Nishida and Fukami, 1989). Four kinds of models were placed at intervals of about 20 cm in an acrylic cage (30ϫ30ϫ30 cm), which had a screened window at one side and a sheet of brown colored paper on the floor.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that electroantennographic responses can be elicited from butterflies with volatiles collected from the leaves of their corresponding host plants (e.g., [19][20][21]). Butterflies can be stimulated to lay eggs on certain plants by specific volatile compounds, as well as deterred from doing so by others (e.g., [22][23][24][25][26][27]). For instance, it was found that the oviposition behavior of female Papilio xuthus can be induced by methanol extracts of fresh leaves of Citrus plants [22], while hydroxybenzoic acid derivatives in a nonhost rutaceous plant deter both oviposition and larval feeding [28].…”
Section: Introductionmentioning
confidence: 99%